A low voltage power cable

By adding composite microcapsules and modified boron nitride to the outer sheath layer of the low-voltage power cable, the problem of termite damage and insufficient thermal conductivity of the outer sheath layer of the cable is solved, and better termite protection, thermal conductivity and flame retardant performance are achieved to ensure the safe and reliable operation of the cable.

CN118571538BActive Publication Date: 2025-04-04HANZHENG CABLE CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410716772.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-04-04
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The outer sheath layer of existing low-voltage power cables is easily damaged by termites and has insufficient thermal conductivity, which leads to the cables being easily heated and affects safe and reliable operation.

Method used

Compound microcapsules and modified boron nitride are added to the masterbatch of the cable outer sheath layer, and the outer sheath layer is formed by direct extrusion method to improve thermal conductivity and flame retardant properties.

Benefits of technology

Effectively prevent termite damage, improve the thermal conductivity and flame retardant performance of the cable, extend the service life of the cable, and ensure the safe and reliable operation of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of power cables, and in particular to a low-voltage power cable. Composite microcapsules and modified boron nitride are added to the raw materials of the outer sheath layer of the power cable, thereby solving the problem that the outer sheath layer of the existing power cable is easily damaged by termites, and the outer sheath layer also has good thermal conductivity and flame retardancy. The composite microcapsules are prepared with chlorfenapyr as the core material, thereby achieving a long-term termite prevention effect. At the same time, the modified carbon nanotubes in the shell material and the boron nitride in the modified boron nitride play a synergistic role, so that the cable outer sheath has a good thermal conductivity effect, and the composite microcapsules and the flame retardant groups in the modified boron nitride work together to make the cable outer sheath have good flame retardancy, and the modified boron nitride can participate in the vulcanization and cross-linking process of low-density polyethylene under the action of an initiator, thereby making the cable outer sheath have better mechanical properties, and the high-hardness cable outer sheath can effectively reduce the damage to the cable outer sheath caused by termites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of power cables, and in particular to a low-voltage power cable. Background Art

[0002] Cross-linked polyethylene low-voltage power cable has the characteristics of easy laying, small footprint, convenient operation and maintenance, and good insulation performance. It has begun to be widely used in my country's urban distribution network. However, with the long-term and high-load operation of the cable, the heating problem of the cable is becoming more and more serious. Cross-linked polyethylene has the disadvantage of low thermal conductivity, which is not conducive to heat dissipation, thus easily causing the cable to heat up, accelerating the growth and aging of cable insulation defects, and having a serious impact on the safe and reliable operation of the cable.

[0003] Termites are worldwide pests, especially in tropical and subtropical regions, where they cause extremely serious damage. Cables generate heat during use, forming a hot and humid environment near the cables, which attracts termites to build nests. Termites gnaw and damage the cable sheath, causing transmission failures, leakage, power outages, and even fires, explosions and other accidents. Therefore, there is an urgent need to improve the heat dissipation and anti-termite performance of power cables. Summary of the invention

[0004] The purpose of the present invention is to provide a low-voltage power cable, which solves the problem that the outer sheath layer of the existing power cable is easily damaged by termites, and the outer sheath layer also has good heat conductivity and flame retardancy.

[0005] The object of the present invention can be achieved by the following technical solution: A low-voltage power cable, characterized in that: from the inside to the outside, it comprises a cable core, an insulation layer and an outer sheath layer;

[0006] The low-voltage power cable is prepared by the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, wrapping with mica tape, twisting, preparing a cable core, wrapping a ceramic composite tape around the outside of the cable core to form an insulating layer, and then using a direct extrusion method to extrude a masterbatch, modified boron nitride and an initiator around the outside of the cable core to form an outer sheath layer, cooling, and vulcanizing to prepare a low-voltage power cable;

[0007] The weight ratio of the masterbatch, modified boron nitride and initiator in the outer sheath layer is 80-100:5-8:0.4-0.6.

[0008] The masterbatch is prepared by the following steps: Step S1: weigh the following masterbatch raw materials in parts by weight: 80-100 parts of low-density polyethylene, 6-10 parts of modified composite microcapsules, 0.2-0.5 parts of antioxidants and 3-5 parts of lubricants;

[0009] Step S2: low-density polyethylene, modified composite microcapsules, antioxidants and lubricants are mixed, and melted at a temperature of 120-130° C. to obtain a masterbatch.

[0010] The composite microcapsules are prepared by the following steps:

[0011] Step A1: ethylenediamine, diethylenetriamine, ethyl acrylate and methanol are mixed, and the mixture is reacted for 5-6 hours at room temperature under nitrogen protection and a stirring rate of 400-500 rpm, and then the pressure is reduced to 260-270 Pa, and the temperature is raised to 140° C. and the mixture is reacted for 6-8 hours to obtain a hyperbranched polyamide;

[0012] The dosage ratio of ethylenediamine, diethylenetriamine and ethyl acrylate is 0.03-0.04 mol: 0.06-0.07 mol: 0.09-0.1 mol;

[0013] During the reaction, at room temperature, the amino groups in ethylenediamine and diethylenetriamine react with the double bonds in ethyl acrylate to form an intermediate, and the amino groups in the intermediate react with the ester groups to form an amide bond under reduced pressure and 140°C to obtain a hyperbranched polyamide with terminal amino groups.

[0014] Step A2: Carboxylated carbon nanotubes, thionyl chloride and N,N-dimethylformamide are mixed, and the mixture is reacted for 20-24 hours at a stirring rate of 300-400 rpm and a temperature of 70° C. to obtain chlorinated carbon nanotubes; the chlorinated carbon nanotubes and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20-30 minutes, and then hyperbranched polyamide and pyridine are added, and the mixture is reacted for 24 hours at a stirring rate of 200-300 rpm and room temperature to obtain modified carbon nanotubes;

[0015] The amount ratio of carboxylated carbon nanotubes and thionyl chloride is 0.8-1g:99.6-132.8g, and the amount ratio of acyl chloride carbon nanotubes, hyperbranched polyamide and pyridine is 0.8-1g:6-8g:0.84-1.06g;

[0016] During the reaction, the carboxyl groups in the carboxylated carbon nanotubes are chlorinated by sulfoxide chloride to obtain chlorinated carbon nanotubes, and the acyl chloride groups in the chlorinated carbon nanotubes react with the amino groups in the hyperbranched polyamide to obtain modified carbon nanotubes.

[0017] Step A3: Mix the modified carbon nanotubes and deionized water and ultrasonically disperse them for 15-20 minutes, stir and add urea, melamine and formaldehyde solution at a stirring rate of 300-400 rpm and a temperature of 70°C, react for 1-2 hours, add triethanolamine to adjust the pH to 8, and prepare a prepolymer, mix chlorfenapyr and cyclohexanone, stir and add sodium dodecyl sulfate and deionized water at a stirring rate of 1100-1200 rpm and a temperature of 70°C, stir for 10-15 minutes, add glacial acetic acid to adjust the pH to 5, and prepare an emulsion, slowly drip the prepolymer into the emulsion, stir and add sodium chloride solution and ammonium chloride at a stirring rate of 600-700 rpm and a temperature of 60°C, then add glacial acetic acid to adjust the pH to 4, and react for 4-5 hours to prepare a composite microcapsule;

[0018] The mass fraction of the formaldehyde solution is 37%, the amount ratio of the modified carbon nanotubes, urea, melamine and formaldehyde solution is 0.1-0.12g: 12-15g: 12.6-15.12g: 100-120g, the amount ratio of chlorfenapyr and sodium dodecyl sulfate is 4.5-5g: 0.4-0.5g, the mass concentration of the sodium chloride solution is 0.1g / mL, and the amount ratio of the prepolymer, emulsion, sodium chloride solution and ammonium chloride is 60-75g: 20-25g: 5-7g: 3-5g;

[0019] During the reaction, the modified carbon nanotubes, urea, and formaldehyde in the amino formaldehyde solution in melamine react to obtain a prepolymer, and an emulsion containing chlorfenapyr is obtained by using an emulsifier, sodium dodecyl sulfate. The prepolymer is dropped into the emulsion, and a composite microcapsule with modified carbon nanotubes-urea-melamine-formaldehyde as a shell material and chlorfenapyr as a core material is obtained by an in-situ-interfacial polymerization method.

[0020] The modified boron nitride is prepared by the following steps:

[0021] Step B1: 2-hydroxyethyl acrylate, phosphorus oxychloride and tetrahydrofuran are mixed, and reacted for 2-3 hours at a stirring rate of 200-300 rpm and 5° C., and then the temperature is raised to 100° C. and 1,1,1-tri(4-hydroxyphenyl)ethane and magnesium chloride are added, and the reaction is continued for 10-12 hours to obtain a hyperbranched polyphosphate;

[0022] The dosage ratio of 2-hydroxyethyl acrylate, phosphorus oxychloride, 1,1,1-tris(4-hydroxyphenyl)ethane and magnesium chloride is 10.4-13g: 25.4g: 71.4-95.2g: 1.2-1.5g;

[0023] During the reaction, at 5°C, the hydroxyl group in 2-hydroxyethyl acrylate undergoes a substitution reaction with the chlorine in phosphorus oxychloride, and then the temperature is raised to 100°C and magnesium chloride is added, so that the other chlorine in phosphorus oxychloride undergoes a substitution reaction with the hydroxyl group in 1,1,1-tri(4-hydroxyphenyl)ethane, thereby obtaining a hyperbranched polyphosphate containing double bonds and hydroxyl groups;

[0024] Step B2: Mixing a hyperbranched polyphosphate, succinic anhydride and dioxane, adding tin chloride, and reacting for 24 hours at a stirring rate of 400-500 rpm and a temperature of 90° C. to obtain a carboxyl-modified polyphosphate; mixing a carboxyl-modified polyphosphate, 3-isocyanatepropyltriethoxysilane and dioxane, and reacting for 10-12 hours at a stirring rate of 400-500 rpm and a temperature of 55° C. to obtain a modified polyphosphate;

[0025] The ratio of hyperbranched polyphosphate, succinic anhydride and tin chloride is 8-10g: 5.6-6.72g: 0.1-0.15g, and the ratio of carboxyl-modified polyphosphate and 3-isocyanate propyltriethoxysilane is 9-11g: 4.4-6.6g;

[0026] During the reaction, under the action of tin chloride, succinic anhydride is ring-opened and reacts with hydroxyl groups in hyperbranched polyphosphate to obtain carboxyl-modified polyphosphate, and the carboxyl groups in the carboxyl-modified polyphosphate react with isocyanate in 3-isocyanate propyltriethoxysilane to obtain modified polyphosphate;

[0027] Step B3: mixing boron nitride powder and sodium hydroxide solution, reacting for 12 hours at a stirring rate of 500-600 rpm and a temperature of 120° C. to obtain activated boron nitride, mixing activated boron nitride, acetone and hydrochloric acid solution and ultrasonically dispersing for 40-50 minutes, stirring at a stirring rate of 500-600 rpm and a temperature of 55° C. and adding modified polyphosphate, reacting for 4-6 hours to obtain modified boron nitride;

[0028] The molar concentration of the sodium hydroxide solution is 5 mol / L, the amount ratio of boron nitride powder to the sodium hydroxide solution is 1.5-2 g:102 g, the molar concentration of the hydrochloric acid solution is 0.001 mol / L, the volume ratio of acetone to the hydrochloric acid solution is 9:1, and the amount ratio of activated boron nitride to modified polyphosphate is 1.5-2 g:15-20 g;

[0029] During the reaction, the boron nitride powder is activated in a sodium hydroxide solution to obtain activated boron nitride having more reactive hydroxyl groups, and the ethoxy groups in the modified polyphosphate are hydrolyzed under acidic conditions and react with the reactive hydroxyl groups in the activated boron nitride to obtain modified boron nitride;

[0030] Beneficial effects of the invention: The present invention relates to the field of power cables, and specifically to a low-voltage power cable. By adding composite microcapsules and modified boron nitride to the raw materials of the outer sheath layer of the power cable, the problem that the outer sheath layer of the existing power cable is easily damaged by termites is solved, and the outer sheath layer also has good thermal conductivity and flame retardancy. Since the composite microcapsules use chlorfenapyr as the core material, it will be gradually released during the use of the power cable, thereby achieving a long-term termite prevention effect. At the same time, since the shell material of the composite microcapsules contains modified carbon nanotubes, and the carbon nanotubes and the boron nitride in the modified boron nitride are both good thermal conductive materials, they play a synergistic role in the outer sheath of the cable. A heat-conducting network structure is formed in the layer, so that the cable outer sheath has a good heat-conducting effect, and then the cable outer sheath layer has a good heat-aging resistance. In addition, since the composite microcapsules contain a large number of triazine groups, they work together with the phosphate groups in the modified boron nitride to make the cable outer sheath layer have a good flame retardant ability. The modified boron nitride also contains a large number of unsaturated double bonds. These double bonds enable the modified boron nitride to participate in the vulcanization and cross-linking process of low-density polyethylene under the action of an initiator, thereby making the cable outer sheath layer have better mechanical properties. The high hardness of the cable outer sheath can effectively reduce the damage to the cable outer sheath caused by termites. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1 A low-voltage power cable, characterized in that: from the inside to the outside, it comprises a cable core, an insulation layer and an outer sheath layer;

[0033] The low-voltage power cable is prepared by the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, wrapping with mica tape, twisting, preparing a cable core, wrapping a ceramic composite tape around the outside of the cable core to form an insulating layer, and then using a direct extrusion method to extrude a masterbatch, modified boron nitride and an initiator around the outside of the cable core to form an outer sheath layer, cooling, and vulcanizing to prepare a low-voltage power cable;

[0034] The weight ratio of the masterbatch, modified boron nitride and dicumyl peroxide initiator in the outer sheath layer is 80:5:0.4;

[0035] The masterbatch is prepared by the following steps: Step S1: weigh the following masterbatch raw materials in parts by weight: 80 parts of commercially available LDPE 2426 low-density polyethylene, 6 parts of modified composite microcapsules, 0.2 parts of 1010 antioxidant and 3 parts of microcrystalline wax lubricant;

[0036] Step S2: mixing low-density polyethylene, modified composite microcapsules, antioxidants and lubricants, and kneading and melting them at a temperature of 120° C. to obtain a masterbatch;

[0037] The composite microcapsules are prepared by the following steps:

[0038] Step A1: ethylenediamine, diethylenetriamine, ethyl acrylate and methanol were mixed, and the mixture was reacted for 5 hours at room temperature under nitrogen protection and a stirring rate of 400 rpm, and then the pressure was reduced to 260 Pa, and the temperature was raised to 140° C. and the mixture was reacted for 6 hours to obtain a hyperbranched polyamide;

[0039] The ratio of ethylenediamine, diethylenetriamine and ethyl acrylate is 0.03 mol: 0.06 mol: 0.09 mol;

[0040] Step A2: Mix commercially available Xianfeng XFD03 carboxylated carbon nanotubes, thionyl chloride and N,N-dimethylformamide, and react for 20 hours at a stirring rate of 3000 rpm and a temperature of 70°C to obtain chlorinated carbon nanotubes, mix the chlorinated carbon nanotubes and N,N-dimethylformamide and ultrasonically disperse them for 20 minutes, then add hyperbranched polyamide and pyridine, and react for 24 hours at a stirring rate of 200 rpm and room temperature to obtain modified carbon nanotubes;

[0041] The ratio of carboxylated carbon nanotubes to thionyl chloride is 0.8 g:99.6 g, and the ratio of acyl chloride carbon nanotubes, hyperbranched polyamide and pyridine is 0.8 g:6 g:0.84 g;

[0042] Step A3: The modified carbon nanotubes and deionized water are mixed and ultrasonically dispersed for 15 minutes. Under the conditions of a stirring rate of 300 rpm and a temperature of 70°C, urea, melamine and formaldehyde solutions are stirred and added, and the reaction is carried out for 1 hour. Triethanolamine is added to adjust the pH to 8 to obtain a prepolymer. Chlorfenapyr and cyclohexanone are mixed. Under the conditions of a stirring rate of 1100 rpm and a temperature of 70°C, sodium dodecyl sulfate and deionized water are stirred and added. The stirring is carried out for 10 minutes. Glacial acetic acid is added to adjust the pH to 5 to obtain an emulsion. The prepolymer is slowly dripped into the emulsion. Under the conditions of a stirring rate of 600 rpm and a temperature of 60°C, sodium chloride solution and ammonium chloride are stirred and added. Glacial acetic acid is added to adjust the pH to 4. The reaction is carried out for 4 hours to obtain a composite microcapsule.

[0043] The mass fraction of formaldehyde solution is 37%, the amount ratio of modified carbon nanotubes, urea, melamine and formaldehyde solution is 0.1g:12g:12.6g:100g, the amount ratio of chlorfenapyr and sodium dodecyl sulfate is 4.5g:0.4g, the mass concentration of sodium chloride solution is 0.1g / mL, and the amount ratio of prepolymer, emulsion, sodium chloride solution and ammonium chloride is 60g:20g:5g:3g;

[0044] The modified boron nitride is prepared by the following steps:

[0045] Step B1: 2-hydroxyethyl acrylate, phosphorus oxychloride and tetrahydrofuran were mixed, and the mixture was reacted for 2 h at a stirring rate of 200 rpm and 5° C., and then the mixture was heated to 100° C. and 1,1,1-tri(4-hydroxyphenyl)ethane and magnesium chloride were added, and the reaction was continued for 10 h to obtain a hyperbranched polyphosphate;

[0046] The amount ratio of 2-hydroxyethyl acrylate, phosphorus oxychloride, 1,1,1-tris(4-hydroxyphenyl)ethane and magnesium chloride is 10.4g:25.4g:71.4g:1.2g;

[0047] Step B2: Mix the hyperbranched polyphosphate, succinic anhydride and dioxane, add tin chloride, and react for 24 hours at a stirring rate of 400 rpm and a temperature of 90° C. to obtain a carboxyl-modified polyphosphate; mix the carboxyl-modified polyphosphate, 3-isocyanatepropyltriethoxysilane and dioxane, and react for 10 hours at a stirring rate of 400 rpm and a temperature of 55° C. to obtain a modified polyphosphate;

[0048] The ratio of hyperbranched polyphosphate, succinic anhydride and tin chloride is 8g:5.6g:0.1g, and the ratio of carboxyl-modified polyphosphate and 3-isocyanatepropyltriethoxysilane is 9g:4.4g;

[0049] Step B3: Mix the commercially available Chengyue 1000 boron nitride powder and sodium hydroxide solution, react for 12 hours at a stirring rate of 500 rpm and a temperature of 120°C to obtain activated boron nitride, mix the activated boron nitride, acetone and hydrochloric acid solution and ultrasonically disperse for 40 minutes, stir and add modified polyphosphate at a stirring rate of 500 rpm and a temperature of 55°C, and react for 4 hours to obtain modified boron nitride;

[0050] The molar concentration of the sodium hydroxide solution is 5 mol / L, the amount ratio of boron nitride powder to the sodium hydroxide solution is 1.5 g:102 g, the molar concentration of the hydrochloric acid solution is 0.001 mol / L, the volume ratio of acetone to the hydrochloric acid solution is 9:1, and the amount ratio of activated boron nitride to modified polyphosphate is 1.5 g:15 g.

[0051] Embodiment 2 A low-voltage power cable, characterized in that: from the inside to the outside, it comprises a cable core, an insulation layer and an outer sheath layer;

[0052] The low-voltage power cable is prepared by the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, wrapping with mica tape, twisting, preparing a cable core, wrapping a ceramic composite tape around the outside of the cable core to form an insulating layer, and then using a direct extrusion method to extrude a masterbatch, modified boron nitride and an initiator around the outside of the cable core to form an outer sheath layer, cooling, and vulcanizing to prepare a low-voltage power cable;

[0053] The weight ratio of the masterbatch, modified boron nitride and dicumyl peroxide initiator in the outer sheath layer is 100:5:0.6.

[0054] The masterbatch is prepared by the following steps: Step S1: weigh the following masterbatch raw materials in parts by weight: 100 parts of commercially available LDPE 2426 low-density polyethylene, 6 parts of modified composite microcapsules, 0.5 parts of 1010 antioxidant and 5 parts of microcrystalline wax lubricant;

[0055] Step S2: mixing low-density polyethylene, modified composite microcapsules, antioxidants and lubricants, and kneading and melting them at a temperature of 130° C. to obtain a masterbatch;

[0056] The composite microcapsules are prepared by the following steps:

[0057] Step A1: ethylenediamine, diethylenetriamine, ethyl acrylate and methanol were mixed, and the mixture was reacted for 6 hours at room temperature under nitrogen protection and a stirring rate of 500 rpm, and then the pressure was reduced to 260 Pa, and the temperature was raised to 140° C. and the mixture was reacted for 8 hours to obtain a hyperbranched polyamide;

[0058] The ratio of ethylenediamine, diethylenetriamine and ethyl acrylate is 0.03 mol: 0.07 mol: 0.09 mol;

[0059] Step A2: Mix commercially available Xianfeng XFD03 carboxylated carbon nanotubes, thionyl chloride and N,N-dimethylformamide, and react for 24 hours at a stirring rate of 400 rpm and a temperature of 70°C to obtain chlorinated carbon nanotubes, mix the chlorinated carbon nanotubes and N,N-dimethylformamide and ultrasonically disperse them for 20 minutes, then add hyperbranched polyamide and pyridine, and react for 24 hours at a stirring rate of 300 rpm and room temperature to obtain modified carbon nanotubes;

[0060] The amount ratio of carboxylated carbon nanotubes and thionyl chloride is 0.8g:132.8g; the amount ratio of acyl chloride carbon nanotubes, hyperbranched polyamide and pyridine is 1g:6g:1.06g;

[0061] Step A3: The modified carbon nanotubes and deionized water are mixed and ultrasonically dispersed for 20 minutes. Under the conditions of a stirring rate of 300 rpm and a temperature of 70°C, urea, melamine and formaldehyde solution are stirred and added, and the reaction is carried out for 2 hours. Triethanolamine is added to adjust the pH to 8 to obtain a prepolymer. Chlorfenapyr and cyclohexanone are mixed. Under the conditions of a stirring rate of 1100 rpm and a temperature of 70°C, sodium dodecyl sulfate and deionized water are stirred and added. The stirring is carried out for 15 minutes. Glacial acetic acid is added to adjust the pH to 5 to obtain an emulsion. The prepolymer is slowly dripped into the emulsion. Under the conditions of a stirring rate of 600 rpm and a temperature of 60°C, sodium chloride solution and ammonium chloride are stirred and added. Glacial acetic acid is added to adjust the pH to 4. The reaction is carried out for 5 hours to obtain a composite microcapsule.

[0062] The mass fraction of formaldehyde solution is 37%, the amount ratio of modified carbon nanotubes, urea, melamine and formaldehyde solution is 0.1g:15g:12.6g:120g, the amount ratio of chlorfenapyr and sodium dodecyl sulfate is 5g:0.4g, the mass concentration of sodium chloride solution is 0.1g / mL, and the amount ratio of prepolymer, emulsion, sodium chloride solution and ammonium chloride is 60g:25g:5g:5g;

[0063] The modified boron nitride is prepared by the following steps:

[0064] Step B1: 2-hydroxyethyl acrylate, phosphorus oxychloride and tetrahydrofuran were mixed, and the mixture was reacted for 3 hours at a stirring rate of 200 rpm and 5° C., and then the mixture was heated to 100° C. and 1,1,1-tri(4-hydroxyphenyl)ethane and magnesium chloride were added, and the reaction was continued for 10 hours to obtain a hyperbranched polyphosphate;

[0065] The ratio of 2-hydroxyethyl acrylate, phosphorus oxychloride, 1,1,1-tris(4-hydroxyphenyl)ethane and magnesium chloride is 13g:27.5g:95.2g:1.2g;

[0066] Step B2: Mix the hyperbranched polyphosphate, succinic anhydride and dioxane, add tin chloride, and react for 24 hours at a stirring rate of 500 rpm and a temperature of 90° C. to obtain a carboxyl-modified polyphosphate; mix the carboxyl-modified polyphosphate, 3-isocyanatepropyltriethoxysilane and dioxane, and react for 12 hours at a stirring rate of 400 rpm and a temperature of 55° C. to obtain a modified polyphosphate;

[0067] The ratio of hyperbranched polyphosphate, succinic anhydride and tin chloride is 8g:6.72g:0.1g, and the ratio of carboxyl-modified polyphosphate and 3-isocyanatepropyltriethoxysilane is 9g:6.66g;

[0068] Step B3: Mix the commercially available Chengyue 1000 boron nitride powder and sodium hydroxide solution, react for 12 hours at a stirring rate of 600 rpm and a temperature of 120°C to obtain activated boron nitride, mix the activated boron nitride, acetone and hydrochloric acid solution and ultrasonically disperse for 40 minutes, stir and add modified polyphosphate at a stirring rate of 500 rpm and a temperature of 55°C, and react for 6 hours to obtain modified boron nitride;

[0069] The molar concentration of the sodium hydroxide solution is 5 mol / L, the amount ratio of boron nitride powder to the sodium hydroxide solution is 2 g:102 g, the molar concentration of the hydrochloric acid solution is 0.001 mol / L, the volume ratio of acetone to the hydrochloric acid solution is 9:1, and the amount ratio of activated boron nitride to modified polyphosphate is 1.5 g:20 g.

[0070] Embodiment 3 A low-voltage power cable, characterized in that: from the inside to the outside, it comprises a cable core, an insulation layer and an outer sheath layer;

[0071] The low-voltage power cable is prepared by the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, wrapping with mica tape, twisting, preparing a cable core, wrapping a ceramic composite tape around the outside of the cable core to form an insulating layer, and then using a direct extrusion method to extrude a masterbatch, modified boron nitride and an initiator around the outside of the cable core to form an outer sheath layer, cooling, and vulcanizing to prepare a low-voltage power cable;

[0072] The weight ratio of the masterbatch, modified boron nitride and dicumyl peroxide initiator in the outer sheath layer is 100:8:0.6.

[0073] The masterbatch is prepared by the following steps: Step S1: weigh the following masterbatch raw materials in parts by weight: 100 parts of commercially available LDPE 2426 low-density polyethylene, 10 parts of modified composite microcapsules, 0.5 parts of 1010 antioxidant and 5 parts of microcrystalline wax lubricant;

[0074] Step S2: mixing low-density polyethylene, modified composite microcapsules, antioxidants and lubricants, and kneading and melting them at a temperature of 130° C. to obtain a masterbatch;

[0075] The composite microcapsules are prepared by the following steps:

[0076] Step A1: ethylenediamine, diethylenetriamine, ethyl acrylate and methanol were mixed, and the mixture was reacted for 6 hours at room temperature under nitrogen protection and a stirring rate of 500 rpm, and then the pressure was reduced to 260 Pa, and the temperature was raised to 140° C. and the mixture was reacted for 8 hours to obtain a hyperbranched polyamide;

[0077] The ratio of ethylenediamine, diethylenetriamine and ethyl acrylate is 0.04 mol: 0.07 mol: 0.1 mol;

[0078] Step A2: Mix commercially available Xianfeng XFD03 carboxylated carbon nanotubes, thionyl chloride and N,N-dimethylformamide, and react for 24 hours at a stirring rate of 400 rpm and a temperature of 70°C to obtain chlorinated carbon nanotubes, mix the chlorinated carbon nanotubes and N,N-dimethylformamide and ultrasonically disperse them for 30 minutes, then add hyperbranched polyamide and pyridine, and react for 24 hours at a stirring rate of 300 rpm and room temperature to obtain modified carbon nanotubes;

[0079] The ratio of carboxylated carbon nanotubes to thionyl chloride is 1 g:132.8 g, and the ratio of acyl chloride carbon nanotubes, hyperbranched polyamide and pyridine is 1 g:8 g:1.06 g;

[0080] Step A3: The modified carbon nanotubes and deionized water are mixed and ultrasonically dispersed for 20 minutes. Under the conditions of a stirring rate of 400 rpm and a temperature of 70°C, urea, melamine and formaldehyde solution are stirred and added, and the reaction is carried out for 2 hours. Triethanolamine is added to adjust the pH to 8 to obtain a prepolymer. Chlorfenapyr and cyclohexanone are mixed. Under the conditions of a stirring rate of 1200 rpm and a temperature of 70°C, sodium dodecyl sulfate and deionized water are stirred and added. The stirring is carried out for 15 minutes. Glacial acetic acid is added to adjust the pH to 5 to obtain an emulsion. The prepolymer is slowly dripped into the emulsion. Under the conditions of a stirring rate of 700 rpm and a temperature of 60°C, sodium chloride solution and ammonium chloride are stirred and added. Glacial acetic acid is added to adjust the pH to 4. The reaction is carried out for 5 hours to obtain a composite microcapsule.

[0081] The mass fraction of formaldehyde solution is 37%, the amount ratio of modified carbon nanotubes, urea, melamine and formaldehyde solution is 0.12g:15g:15.12g:120g, the amount ratio of chlorfenapyr and sodium dodecyl sulfate is 5g:0.5g, the mass concentration of sodium chloride solution is 0.1g / mL, and the amount ratio of prepolymer, emulsion, sodium chloride solution and ammonium chloride is 75g:25g:7g:5g;

[0082] The modified boron nitride is prepared by the following steps:

[0083] Step B1: 2-hydroxyethyl acrylate, phosphorus oxychloride and tetrahydrofuran were mixed, and the mixture was reacted for 3 hours at a stirring rate of 300 rpm and 5° C., and then the mixture was heated to 100° C. and 1,1,1-tri(4-hydroxyphenyl)ethane and magnesium chloride were added, and the reaction was continued for 12 hours to obtain a hyperbranched polyphosphate;

[0084] The ratio of 2-hydroxyethyl acrylate, phosphorus oxychloride, 1,1,1-tris(4-hydroxyphenyl)ethane and magnesium chloride is 13g:27.5g:95.2g:1.5g;

[0085] Step B2: Mix the hyperbranched polyphosphate, succinic anhydride and dioxane, add tin chloride, and react for 24 hours at a stirring rate of 500 rpm and a temperature of 90° C. to obtain a carboxyl-modified polyphosphate; mix the carboxyl-modified polyphosphate, 3-isocyanatepropyltriethoxysilane and dioxane, and react for 12 hours at a stirring rate of 500 rpm and a temperature of 55° C. to obtain a modified polyphosphate;

[0086] The ratio of hyperbranched polyphosphate, succinic anhydride and tin chloride is 10g:6.72g:0.15g, and the ratio of carboxyl-modified polyphosphate and 3-isocyanatepropyltriethoxysilane is 11g:6.66g;

[0087] Step B3: Mix the commercially available Chengyue 1000 boron nitride powder and sodium hydroxide solution, react for 12 hours at a stirring rate of 600 rpm and a temperature of 120°C to obtain activated boron nitride, mix the activated boron nitride, acetone and hydrochloric acid solution and ultrasonically disperse for 50 minutes, stir and add modified polyphosphate at a stirring rate of 600 rpm and a temperature of 55°C, and react for 6 hours to obtain modified boron nitride;

[0088] The molar concentration of the sodium hydroxide solution is 5 mol / L, the amount ratio of boron nitride powder to the sodium hydroxide solution is 2 g:102 g, the molar concentration of the hydrochloric acid solution is 0.001 mol / L, the volume ratio of acetone to the hydrochloric acid solution is 9:1, and the amount ratio of activated boron nitride to modified polyphosphate is 2 g:20 g.

[0089] Comparative Example 1 Compared with Example 3, this comparative example is characterized in that chlorfenapyr in the preparation process of the composite microcapsules in Example 3 is removed, and the other steps are the same.

[0090] Comparative Example 2 Compared with Example 3, this comparative example is different in that the modified carbon nanotubes in the preparation process of the composite microcapsules in Example 3 are replaced with hyperbranched polyamide, and the other steps are the same.

[0091] Comparative Example 3 Compared with Example 3, this comparative example is different in that the modified polyphosphate in the preparation process of modified boron nitride in Example 3 is replaced by hyperbranched polyphosphate, and the other steps are the same.

[0092] Comparative Example 4 Compared with Example 3, this comparative example is different in that the modified boron nitride in Example 3 is replaced by activated boron nitride, and the other steps are the same.

[0093] Take the low-voltage power cables prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, peel off the outer sheath layer to prepare samples, refer to ASTM D 5470-2017, cut the outer sheath layer into 15mm×15mm×4mm samples, measure the thermal conductivity, refer to GB / T 531.1-2008, use a Shore D hardness tester to test the Shore hardness, cut the outer sheath layer into 80mm×25mm×2mm samples, refer to the ant nest method in JB / T 10696.9-2011, measure the anti-termite performance, the experimental period is 12 weeks, take out the sample, and evaluate its anti-termite performance by its termite decay grade. Refer to GB / T 2408-2008, the thickness is 3mm, and the vertical burning performance of the sample is tested by a vertical burning tester, and its flame retardant performance is evaluated by the vertical burning grade. The test results are shown in Table 1 below. Detection performance table:

[0094] Table 1 Detection performance table

[0095]

[0096] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 removes chlorfenapyr during the preparation of the composite microcapsules of Example 3. Due to the lack of chlorfenapyr, its anti-termite performance is significantly reduced. Comparative Example 2 replaces the modified carbon nanotubes with hyperbranched polyamide during the preparation of the composite microcapsules of Example 3. Due to the lack of carbon nanotubes, its thermal conductivity is significantly reduced. Comparative Example 3 replaces the modified polyphosphate ester with hyperbranched polyphosphate ester during the preparation of the modified boron nitride of Example 3. Due to the lack of double bonds, its mechanical properties are significantly reduced, and the reduction in mechanical properties also causes its anti-termite performance to decrease to a certain extent. Comparative Example 4 replaces the modified boron nitride of Example 3 with activated boron nitride. Due to the lack of phosphate groups, its flame retardant properties are significantly reduced.

[0097] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0098] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A low voltage power cable, characterized in that: From inside to outside, there are cable core, insulation layer and outer sheath layer; The low-voltage power cable is prepared by the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, wrapping with mica tape, twisting, preparing a cable core, wrapping a ceramic composite tape around the outside of the cable core to form an insulating layer, and then using a direct extrusion method to extrude a masterbatch, modified boron nitride and an initiator around the outside of the cable core to form an outer sheath layer, cooling, and vulcanizing to prepare a low-voltage power cable; The weight ratio of masterbatch, modified boron nitride and initiator in the outer sheath layer is 80-100: 5-8: 0.4-0.6; The masterbatch is prepared by the following steps: Step S1: weigh the following masterbatch raw materials in parts by weight: 80-100 parts of low-density polyethylene, 6-10 parts of modified composite microcapsules, 0.2-0.5 parts of antioxidants and 3-5 parts of lubricants; Step S2: mixing low-density polyethylene, modified composite microcapsules, antioxidants and lubricants, and kneading and melting them at a temperature of 120-130° C. to obtain a masterbatch; The composite microcapsules are prepared by the following steps: Step A1: ethylenediamine, diethylenetriamine, ethyl acrylate and methanol are mixed, and the mixture is reacted for 5-6 hours at room temperature under nitrogen protection and a stirring rate of 400-500 rpm, and then the pressure is reduced to 260-270 Pa, and the temperature is raised to 140° C., and the mixture is reacted for 6-8 hours to obtain a hyperbranched polyamide; Step A2: Carboxylated carbon nanotubes, thionyl chloride and N,N-dimethylformamide are mixed, and the mixture is reacted for 20-24 hours at a stirring rate of 300-400 rpm and a temperature of 70° C. to obtain chlorinated carbon nanotubes; the chlorinated carbon nanotubes and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20-30 minutes, and then hyperbranched polyamide and pyridine are added, and the mixture is reacted for 24 hours at a stirring rate of 200-300 rpm and room temperature to obtain modified carbon nanotubes; Step A3: The modified carbon nanotubes and deionized water are mixed and ultrasonically dispersed for 15-20 minutes. Under the conditions of stirring rate of 300-400rpm and temperature of 70°C, urea, melamine and formaldehyde solution are stirred and added, and the reaction is carried out for 1-2 hours. Triethanolamine is added to adjust the pH to 8 to obtain a prepolymer. Chlorfenapyr and cyclohexanone are mixed. Under the conditions of stirring rate of 1100-1200rpm and temperature of 70°C, sodium dodecyl sulfate and deionized water are stirred and added. The mixture is stirred for 10-15 minutes. Glacial acetic acid is added to adjust the pH to 5 to obtain an emulsion. The prepolymer is slowly dripped into the emulsion. Under the conditions of stirring rate of 600-700rpm and temperature of 60°C, sodium chloride solution and ammonium chloride are stirred and added. Glacial acetic acid is added to adjust the pH to 4. The reaction is carried out for 4-5 hours to obtain a composite microcapsule.

2. A low voltage power cable according to claim 1, characterized in that: In step A1, the usage ratio of ethylenediamine, diethylenetriamine and ethyl acrylate is 0.03-0.04 mol: 0.06-0.07 mol: 0.09-0.1 mol.

3. A low voltage power cable according to claim 1, characterized in that: In step A2, the ratio of carboxylated carbon nanotubes to thionyl chloride is 0.8-1 g:99.6-132.8 g, and the ratio of acyl chloride carbon nanotubes, hyperbranched polyamide and pyridine is 0.8-1 g:6-8 g:0.84-1.06 g.

4. A low voltage power cable according to claim 1, characterized in that: In step A3: the mass fraction of the formaldehyde solution is 37%, the amount ratio of modified carbon nanotubes, urea, melamine and formaldehyde solution is 0.1-0.12g: 12-15g: 12.6-15.12g: 100-120g, the amount ratio of chlorfenapyr and sodium dodecyl sulfate is 4.5-5g: 0.4-0.5g, the mass concentration of sodium chloride solution is 0.1g / mL, and the amount ratio of prepolymer, emulsion, sodium chloride solution and ammonium chloride is 60-75g: 20-25g: 5-7g: 3-5g.

5. A low voltage power cable according to claim 1, characterized in that: The modified boron nitride is prepared by the following steps: Step B1: 2-hydroxyethyl acrylate, phosphorus oxychloride and tetrahydrofuran are mixed, and the mixture is reacted for 2-3 hours at a stirring rate of 200-300 rpm and 5° C., and then the mixture is heated to 100° C. and 1,1,1-tri(4-hydroxyphenyl)ethane and magnesium chloride are added, and the reaction is continued for 10-12 hours to prepare a hyperbranched polyphosphate; Step B2: Mixing a hyperbranched polyphosphate, succinic anhydride and dioxane, adding tin chloride, and reacting for 24 hours at a stirring rate of 400-500 rpm and a temperature of 90° C. to obtain a carboxyl-modified polyphosphate; mixing a carboxyl-modified polyphosphate, 3-isocyanatepropyltriethoxysilane and dioxane, and reacting for 10-12 hours at a stirring rate of 400-500 rpm and a temperature of 55° C. to obtain a modified polyphosphate; Step B3: Mix boron nitride powder and sodium hydroxide solution, react for 12 hours at a stirring rate of 500-600 rpm and a temperature of 120°C to obtain activated boron nitride, mix the activated boron nitride, acetone and hydrochloric acid solution and ultrasonically disperse for 40-50 minutes, stir and add modified polyphosphate at a stirring rate of 500-600 rpm and a temperature of 55°C, and react for 4-6 hours to obtain modified boron nitride.

6. A low voltage power cable according to claim 5, characterized in that: In step B1, the ratio of 2-hydroxyethyl acrylate, phosphorus oxychloride, 1,1,1-tris(4-hydroxyphenyl)ethane and magnesium chloride is 10.4-13 g: 25.4 g: 71.4-95.2 g: 1.2-1.5 g.

7. A low voltage power cable according to claim 5, characterized in that: In step B2, the ratio of hyperbranched polyphosphate, succinic anhydride and tin chloride is 8-10g: 5.6-6.72g: 0.1-0.15g, and the ratio of carboxyl-modified polyphosphate and 3-isocyanatepropyltriethoxysilane is 9-11g: 4.4-6.6g.

8. A low voltage power cable according to claim 5, characterized in that: In step B3: the molar concentration of the sodium hydroxide solution is 5 mol / L, the amount ratio of boron nitride powder to the sodium hydroxide solution is 1.5-2 g:102 g, the molar concentration of the hydrochloric acid solution is 0.001 mol / L, the volume ratio of acetone to the hydrochloric acid solution is 9:1, and the amount ratio of activated boron nitride to modified polyphosphate is 1.5-2 g:15-20 g.

Citation Information

Patent Citations

  • Polyethylene cable conduit and preparation method thereof

    CN117895413A